A casa e a biblioteca : espaços afetivos regidos pela mulher em obras de Stella Maris Rezende - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This dissertation discusses affection as a spatial extension in a trilogy, by Stella Maris Rezende, composed by: A mocinha do Mercado Central (2011), A sobrinha do poeta (2012) and As gêmeas da família (2013). For over two decades, this author from Minas Gerais has been writing for both youth and adults. However, the thought cut focuses on the elaboration of his literary creation for children and adolescents, since her books are well accepted by critics and young audiences. Her diverse and abundant production is surprising, revealing a writer who favors experimentation through hybridization between textual genres, mixing them with other artistic manifestations, such as cinema, theater and art. These three adult young books discuss the complex human condition from the teenagers perspective. Ahead of this imaginary, they are protagonists who go through the same conflicts of the majority of their reading public, related to the troubled and touchy puberty. In addition to facing the anxieties and uncertainties of this transition, the protagonists still face them, once more imposed by patriarchy and Christian morality. Throughout these three Bildungsroman, some trips are experienced and imagined by Maria Campos, Leodegária Moura and the triplets Maria da Fé, Maria da Esperança and Maria da Caridade. As they move through geographical spaces, they found adversity and otherness and acquire a more acute knowledge of themselves and the other. They discover and manage life's contradictions, such as joy and melancholy, tragedy and magic, dream and reality. In other circumstances, the female figure is at the center of spaces of affection, such as the library. As a mediator, it indicates paths between knowledge and the humanity of those around it. In the narratives, the house, which usually understands the meaning of home, does not have a characteristic as a point of arrival, but always as a port of departure, which causes the search for freedom of the protagonists. For to reach our goal, this research used literary analysis as a methodology. As a theoretical foundation, we use literature studies with Abramovich (1989), Candido (2006), Coelho (2000), Lajolo and Zilberman (2004), Hunt (2010) and Zilberman (2007), of topology and literary space with Bachelard (1990), Borges Filho (2007; 2008), Brandão (2013), Dimas (1987), Lins (1976); feminist criticism Hollanda (1994) and Dalcastagnè (2005; 2008); and identity based mainly on Bauman (2005), Hall (2006). Therefore, when Stella Maris gives the young reader the opportunity to immerse himself in a fictional universe open to scholarship, popular culture, symbology and reflections on taboo themes, his writing disagrees with the predominant patterns of Young Adults literary creation, which often takes care only of aspects of adventures and mysteries.
The house and the library : affective spaces ruled by women, by Stella Maris Rezende works
Keywords: Espaço; Afeto; Gênero; Identidade; Literatura juvenil; Space; Literature Juvenile; Affection; Genre; Identity; Literature juvenile; LINGUISTICA, LETRAS E ARTES